2018
DOI: 10.3892/mmr.2018.9250
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits angiogenesis of the M2‑like TAMs via the downregulation of hypoxia inducible factor‑1α and the STAT3 signalling pathway under hypoxia

Abstract: The imbalance between angiogenic inducers and inhibitors appears to be a critical factor in tumour pathogenesis. Angiogenesis serves a key role in the occurrence, invasion and metastasis of tumours. Macrophages are a major cellular component of human and rodent tumours, where they are usually termed tumour‑associated macrophages (TAMs). In malignant tumours, TAMs tend to resemble alternatively activated macrophages (M2‑like), promote TA angiogenesis, strengthen tumour migration and invasive abilities, and simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Common flavone luteolin suppressed HIF-1 activation within M2-like tumor-associated macrophages (TAMs) under hypoxic conditions [ 138 ].…”
Section: Beneficial Effects Of Flavonoids In the Regulation Of Hypmentioning
confidence: 99%
“…Common flavone luteolin suppressed HIF-1 activation within M2-like tumor-associated macrophages (TAMs) under hypoxic conditions [ 138 ].…”
Section: Beneficial Effects Of Flavonoids In the Regulation Of Hypmentioning
confidence: 99%
“…Studies have shown that plantain can inhibit the expression of HIF-1 α and VEGF and the phosphorylation of protein kinase B (Akt) and downregulate the gene expression of TNF- α and IL-1 β and the activation of NF- κ B to treat diabetic retinal injury [ 51 ]. The compounds dinatin [ 52 ], baicalein [ 53 ], baicalin [ 54 ], and luteolin [ 55 ] have been shown to reduce HIF-1 level. Therefore, HIF-1 α signaling pathway may be the pathway of plantain in the treatment of gouty arthritis, and the specific mechanism and pathway need to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin has high anti-inflammatory activity and can effectively inhibit the expression of NLRP3 by inhibiting IL-17A signal in enteritis tissue [ 100 ]. Luteolin can inhibit the activation of HIF-1 and STAT3 signal and reduce the expression of VEGF and MMP-9 to play anticancer role [ 55 ]. It can inhibit the levels of TNF- α , IL-6, IL-1 β , IL-17, membrane cation-selective receptor channels (P2X4), nucleotide oligomerization domain-like receptor protein 1 (NLRP1), apoptosis-associated speck-like protein containing CARD (ASC), and caspase-1p10 in RA rats induced by Freund's complete adjuvant and reduce the infiltration of inflammatory cells and synovial hyperplasia [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a well-characterized inflammatory transcription factor which can be activated by a wide range of extracellular or intracellular stimuli, including IL-6 family members IL-6, IL-11, IL-27, leukemia inhibitory factor, IL-10 family members IL-10, IL-22, epidermal growth factor, VEGF, or environmental stimuli such as hypoxia or glucose deprivation [Carlsson et al, 2018;Fang et al, 2018]. Many evidences have indicated that overactivation of STAT3 signaling is associated with the initiation or progression of endothelial inflammation.…”
Section: Discussionmentioning
confidence: 99%